Post-Keynesian Theory of International Finance - Dittrich, Adam (2021)
The objective of this study is to conduct a methodological introduction to post-Keynesian economics and its comparison to orthodox economics. The main focus is then moved towards the international finance from both the perspective of orthodox and post-Keynesian economics. It includes concise introduction of both strands with more focus on post-Keynesians and the interest rate parity, then a comparison is provided. Afterwards an empirical analysis of post-Keynesians arguments is conducted in uncovered interest partiy, its factors causing deviations, covered interest parity, forward market unbiasedness hypothesis and forward rate prediction errors are analysed. All within the Czech Republic with the exchange rate commitment between 2013 to 2017 taken into account. Author in the first analysis has come to a conclusion that the uncovered interest parity does not hold and that the exchange rate commitment has changed the behaviour of the risk variables. In second analysis, the forward market unbiasedness hypothesis was not proved (forward error rates moved between 47,60 % to 91,88 %) and it has been found that the exchange rate commitment has indirectly influenced the currency pair of CZK/USD. Third analysis shows that the covered interest parity holds and that the forward market unbiasedness hypothesis does not.